2019
DOI: 10.1002/mawe.201800227
|View full text |Cite
|
Sign up to set email alerts
|

Grain morphology and texture evolution of TC21 titanium alloy during annealing with different time

Abstract: A homogeneous equiaxed‐structure TC21 titanium alloy is hot rolled and annealed for different time ranging from 1 h to 6 h. The grain morphology and texture evolution of α and β phases during annealing are mainly investigated using the electron back‐scattered diffraction characterization. In the early annealing stage, the α grain mainly maintains the elongated morphology generated in the rolling. With increasing annealing time, more and more elongated α grains become equiaxed due to enhanced static recrystalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Limited studies have considered the conventional treatments of TC21 titanium alloy [ 25 , 26 , 27 ], whereas scarce studies were reported that investigated laser processing techniques of TC21 alloys, especially direct energy deposition technique. For example, a study on laser peening of TC21 alloy was conducted by Zhigang et al [ 28 ], where this technique induces intensive plastic deformation and high dislocation density to enhance the surface performance of such materials.…”
Section: Introductionmentioning
confidence: 99%
“…Limited studies have considered the conventional treatments of TC21 titanium alloy [ 25 , 26 , 27 ], whereas scarce studies were reported that investigated laser processing techniques of TC21 alloys, especially direct energy deposition technique. For example, a study on laser peening of TC21 alloy was conducted by Zhigang et al [ 28 ], where this technique induces intensive plastic deformation and high dislocation density to enhance the surface performance of such materials.…”
Section: Introductionmentioning
confidence: 99%